Survival strategies of education-related non governmental organisation in post-apartheid Sout Africa - Kaniki, Phoebe Nsunge (My University, 2008)
ABSTRACT The study explores strategies employed by surviving education-related NGOs – strategies that have enabled them to continue to survive in the post apartheid South African era. Using primarily in-depth interviews, the study found that surviving NGOs have had to make several sacrifices and changes. These include transforming modes of operations diversification; the shedding of some activities; becoming more competitive and adopting more businesslike methods of operation, such as introducing new stringent administrative and financial management systems. As well, successful NGOs employed better systematic planning and implementation systems; expanded from single donor funding reliance to multiple donor sources. The study also makes some recommendations. These include better collaborative partnerships among the various stakeholders – government, NGOs, donors and private sector – which need to be further nurtured; It is imperative for NGOs to become more flexible in the activities and services they offer and they must be ready to transform themselves when necessary. Collaborative partnerships among NGOs are very important to enhance each other services and function as a united front. As well, there is a need for the government to review tendering processes, and NGOs need to put in place monitoring & evaluation systems to support and ensure effective implementation of strategic plans.
Keywords: NGOs South Africa; educational NGOs